Patellofemoral joint kinematics: The circular path of the patella around the trochlear axis - Iranpour, F.; Merican, A.M.; Rodriguez Ybaena, F.; Cobb, J.P.; Amis, A.A. (Elsevier, 2010)
Differing descriptions of patellar motion relative to the femur have resulted from previous studies. We hypothesized that patellar kinematics would correlate to the trochlear geometry and that differing descriptions could be reconciled by accounting for differing alignments of measurement axes. Seven normal fresh-frozen knees were CT scanned, and their kinematics with quadriceps loading was measured by an optical tracker system. Kinematics was calculated in relation to the femoral epicondylar, anatomic, and mechanical axes. A novel trochlear axis was defined, between the centers of spheres best fitted to the medial and lateral trochlear articular surfaces. The path of the center of the patella was circular and uniplanar (root-mean-square error 0.3 mm) above 16 +/- 3 degrees (mean +/- SD) knee flexion. In the coronal plane, this circle was aligned 6 +/- 2 degrees from the femoral anatomical axis, close to the mechanical axis alignment. It was 91 +/- 3 degrees from the epicondylar axis, and 88 +/- 3 degrees from the trochlear axis. In the transverse plane it was 91 +/- 3 degrees and 88 +/- 3 degrees from the epicondylar and trochlear axes, respectively. Manipulation of the data to different axis alignments showed that differing previously published data could be reconciled. The circular path of patellar motion around the trochlea, aligned with the mechanical axis of the leg, is easily visualized and understood. (C) 2009 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 28:589-594, 2010